AVALIAÇÃO COMPARATIVA DO CONFORTO TÉRMICO RESULTANTE DA CARTA BIOCLIMÁTICA DE GIVONI COM DADOS DE PESQUISA DE SENSAÇÃO TÉRMICA EM RESIDÊNCIAS EM FLORIANÓPOLIS - Abreu, Ana Lígia Papst de; Dal’ Annio, Lorena Binhoti; Nardi, Aline Souza Lopes Ventura; Klein, Gustavo Menna Barreto (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In this study, the residential buildings thermal comfort in Florianópolis was investigated based on field research of thermal sensation. The aim of this paper is to compare the thermal sensation of residential dwellers in Florianópolis with the comfort zone results presented by the Givoni Bioclimatic Chart. The data of the field study were organized by the thermal sensation, while the hourly internal data (temperature and relative humidity) had been plotted in Givoni Bioclimatic Chart. The comparison, of the field study with the results of hourly data plotted on the Givoni Bioclimatic Chart, has showed that the dwellers have an acceptance of comfort superior to those delimited by comfort area in the bioclimatic Chart. Although the quantitative values of the Analysis Bio software report have not corresponded to the field survey data, the plotted of the internal climatic data enables the evaluation of the thermal comfort if considering the ventilation zone also comfort zone.